Analysis of Weak Position in Overhead line under Heavy Icing Condition by Finite Element Method - Gan Yan; Liu Chao; Ruan Jiangjun; Li Jinliang; Du Zhiye; Hu Yuanchao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Transmission tower is an important component of power system, and heavy iced transmission line has became one of the important factors against its safety and stability in China's power system these years but the transmission line designed from traditional standard can't endure the more worse environment. In this paper, for positioning the weak points of the transmission line under heavy icing accurately and providing accurate positional parameters to online monitoring devices, the strain section model is built to analysis their mechanical properties under icing and wind conditions .In proposed method, the coupling effect between tower and lines is considered, then the weak tower is picked out by strain section model that is combined with eight towers. The single one-tower-two-lines model of weak tower is built to simulate and verify the weak point accurately. Finally the better way is defined to get the location of weak structure combined with the advantages of both models.